A legal study on the rights of the prisoners in Malaysia with special reference to the right of prisoners to complaint and grievances, living in adequate prison condition, medical treatment, conjugal visits, and voting / Bazlilah Mohd Bukhari … [et al.] - Mohd Bukhari, Bazlilah; Mohamad Said, Noor Amalina Shazaleen; Nordin, Norhazwani; Abd Razak, Siti Sarah (2009)
This is a research project conducted to determine the rationality of the right given to the prisoners in respect of medical treatment, right to conjugal visits, right to vote and to complaint and the prison condition itself. Basically, even the prisoners are the one who had been detained as a punishment for their wrongful conduct or an offence that they had done, the right of the prisoners are not explicitly taken away by the fact of imprisonment. Even though their freedom of movement is curtailed, they are still subjected to the protection of rights same as one who is not being detained. In Malaysia, it has been enumerated in Part II of the Federal Constitution, which stated that no person shall be deprived of his life or personal liberty saves in accordance with law. These provisions are applicable to the prisoners too because a prisoner remains a 'person' in the prison. There was Article 5 of the Federal Constitution that laid down the protection towards personal liberty and Article 8 that outline that all people are subjected to equality before the law and being treated equally. Besides that, there are Prisons Act 1995 and Prison Regulations 2000 to govern the right of the prisoners. However, all this above provision does not provide absolute protection to the prisoners, as there are still subject to certain denial and restrictions being imposed by the government on the reason of ineligibility and unqualified. They are often argued that the prisoners are put in an unusual legal position where some of their right had been denied. The prisoner's right and the extent to which they are able to contact and engaged with the outside world are defined and limited by a mass of rules and regulations. Many things are taken for granted outside are privileges which have to be fought by a prisoners. Every country is urged to take an action as rule of law is to mean anything. Therefore, it has to mean that the prison system is no less answerable to the courts than any other limb of the state, but both for how it serves and protects the prisoner's right.